LEADERSHIP IN HIGHER EDUCATION A CASE STUDY AT THE UNIVERSITY OF WEST SULAWESI (Revista Galega de Economía)
This research aims to examine the effects that result from the manner in which leaders operate within a higher education establishment?  The role of a leader is to manage, coordinate, influence and motivate the people he leads to achieve organizational goals. However, lack of attention from the leadership at the university to their Subordinates, presents various problems from various aspects. This study is explanatory-causality research with a quantitative approach to explain more concerning the effect of leadership style on other variables. The data collection method is in the form of a survey with Questionnaires distributed to the university academic community (except the Chancellor). The data is processed by analysis techniques Partial Least Square (PLS). We found various findings regarding the impact of leadership on important aspects of determining the performance of its academic community. We also discuss these aspects in a more comprehensive manner using the perspective of Higher education institutions. Another factor that might have contributed to this finding was the lack of coordination meetings between leaders, therefore the issues were not clearly detected, and the things that were done gave the impression â€˜up in the airâ€™. It is important for leaders at university to pay more attention to internal issues first before focusing on achieving the organization's large-scale vision and missions, since the performance of higher education is highly dependent on the performance of its human resources.